The Electronic Structure of the Al3− Anion: Is it Aromatic?. Issue 27 (5th June 2015) - Mercero, Jose M.; Matito, Eduard; Ruipérez, Fernando; Infante, Ivan; Lopez, Xabier; Ugalde, Jesus M.
Abstract Multiconfigurational high‐level electronic structure calculations show that the <alternatives> <![CDATA[Al- 3]]> <inline-graphic xlink:href="ark:/27927/pgj12qccjgn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> ring‐like cluster anion has three close low‐lying electronic states of different spin, all of them having strong multiconfigurational character. The aromaticity of the cluster has, therefore, been studied by means of total electron delocalization and normalized multicenter electron delocalization indices evaluated from the multiconfigurational wave functions of each state. The lowest‐lying singlet and triplet states are found to be highly aromatic, whereas the next lowest‐lying state, the quintet state, has much less, though non‐negligible, aromatic character.